Ethnomedicinal, Phytochemical and Pharmacological Investigations of Tetradenia riparia (Hochst.) Codd (Lamiaceae) - Panda, Sujogya Kumar; Gazim, Zilda Cristiani; Swain, Shasank S.; Bento, Marisa Cassia Vieira de Araujo; Sena, Jéssica da Silva; Mukazayire, Marie Jeanne; Van Puyvelde, Luc; Luyten, Walter (Frontiers in Pharmacology, 2022)
Tetradenia riparia Hochsteter codd. (Lamiaceae) in its native African continent, is considered one of the most popular aromatic medicinal plants. In folk medicine it may be used as an infusion to treat respiratory problems, cough, headache, stomach pain, diarrhea, fever, malaria, and dengue; and in the form of compresses it is applied for the relief of headaches and toothaches. The species T. riparia has been researched for decades to isolate and identify chemical constituents present in extracts or essential oil obtained from the leaves, floral buds, or stems of this plant. The present study reviews the scientific literature on ethnomedicinal, phytochemical, and pharmacological aspects of T. riparia. We discuss issues related to the botanical and geographical description of the species, ethnobotanical uses, phytochemical studies on its essential oil and extracts, and biological activities of T. riparia. Several compounds have already been isolated from leaves, such as ibozol, 7α-hydroxyroileanone, 1',2'-dideacetylboronolide, 8(14),15-sandaracopimaradiene-7α,18-diol; 5,6-dihydro-α-pyrone and α-pyrone. Terpenes predominated in the essential oil, comprising monoterpenes, sesquiterpenes, diterpenes, hydrocarbons, and oxygenates. Most phytocompounds were isolated from the leaves and flower buds, namely fenchone, 14-hydroxy-9-epi (E)-caryophyllene, 9β, 13β-epoxy-7-abietene, and 6,7-dehydroroileanone. These compounds provide the species a high pharmacological potential, with antimicrobial, antioxidant, antitumor, analgesic, anti-leishmania, anti-tuberculosis, and anti-parasitic activities. Therefore, this species is a promising herbal medicine.